What Do Closed Mountain Roads Tell Us About Territories? A Critical Analysis of Abandonment, Re-Appropriation and Valorisation in the Vercors (19th-21st Century) - Emma-Sophie Mouret (Revue de Géographie Alpine)
In the Alps, mountain roads offer clear examples of the 19th-century policy of modernising road networks. In the middle of the 1800s, the Vercors mountain range in the French departments of Isère and Drôme was criss-crossed by a network of carriageable roads. Most of these roads were built to transport wood but rapidly became tourist routes. After the Second World War, the roads started being used more and more as daily transit increased. At the end of the 1970s, however, the risk of landslides was increasingly becoming an issue. Some of the roads were closed following landslides or after the construction of safer and faster roads. At the time they were built, these roads were symbols of modernity. Later, as they became obsolete, they came to embody both the development strategies of territories and the legacy of former policies of modernisation. Now, this closed roads aren’t showed alongside other “magnificent roads”.